A condição humana e as disposições sobre o bem e o mal em Bhagavadgītā - Tomimatsu, Célia Maki (2013)
The object of this research is an investigation about the disposition of good and evil in the Hindu text Bhagavadgītā, which passage is inserted in Book VI of the Indian epic Mahābhārata. The goal is to reflect about the human condition that permeates the passage of Bhagavadgītā, about the ideas of good and evil, especially in the context of the dialogue between the main characters of this chapter: the god Kṛṣṇa and his friend Arjuna, the Pāṇḍava worrier. The hypothesis is that, in this epic, neither the dialogue nor the narrated battle, represent an external action of an individual, but, due to the concept of dharma in Hinduism, an inside;